2014
DOI: 10.1210/jc.2014-1718
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Risk of Osteoporosis: A Population-Based Cohort Study in Taiwan

Abstract: People diagnosed with OSA are at increased risk for subsequent osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 34 publications
1
66
1
Order By: Relevance
“…[1][2][3][4] Extensive evidence has shown that sleep disturbance is an independent risk factor of increased overall mortality, 5 increased psychiatric and medical morbidity, 6,7 decreased physical and cognitive function, 8,9 and decreased health-related quality of life (HRQOL) 10,11 among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Extensive evidence has shown that sleep disturbance is an independent risk factor of increased overall mortality, 5 increased psychiatric and medical morbidity, 6,7 decreased physical and cognitive function, 8,9 and decreased health-related quality of life (HRQOL) 10,11 among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep apnea is common in the general population 1 and is associated with severe health problems, such as cognitive dysfunction, 2 diabetes, 3 osteoporosis, 4 hypertension, 5 cardiovascular diseases, and mortality. 6 Sleep apnea also shares several symptoms with depression, such as fatigue, disturbed sleep, irritability, depressed mood, and poor concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers report a vicious circle between vitamin D deficiency, OSAS, and glucose metabolism: patients with severe OSAS had lower vitamin D levels [68], the risk of osteoporosis in the OSAS cohort was 2.74 times than patients without sleep disorders [69], and recently some authors reported that vitamin D deficiency (closely linked to osteoporosis and diabetes) may play a role and worsen OSAS's adverse outcomes and comorbidities, especially those regarding glucose metabolism [70,71].…”
Section: Osas and Bone Metabolismmentioning
confidence: 99%